Hounsfield unit value and clot length in the acutely occluded vessel and time required to achieve thrombectomy, complications and outcome. (31st July 2013) - Spiotta, Alejandro M; Vargas, Jan; Hawk, Harris; Turner, Raymond; Chaudry, M Imran; Battenhouse, Holly; Turk, Aquilla S
Abstract : Introduction: Intra-arterial therapy for acute ischemic stroke (AIS) now has an established role. We investigated if Hounsfield Units (HU) quantification on non-contrast CT is associated with ease and efficacy of mechanical thrombectomy and outcomes. Methods: We retrospectively studied a prospectively maintained database of cases of AIS given intra-arterial therapy between May 2008 and August 2012. Functional outcome was assessed by 90-day follow-up modified Rankin Scale (mRS). Patients were dichotomized based on time to recanalization. HU were calculated on head CT and thrombus location and length were determined on CT angiography. Simple linear regression was used to analyze the association between clot length, average HU and other clinical variables. Results: 141 patients were included. There was no difference in clot length or average HU among patients with good recanalization achieved within 1 h and those in which the procedures extended beyond 1 h. There was no relationship between clot length or density and recanalization. The thrombus length and density were not significantly different between patients with procedural complications and those without. Neither the presence of post-procedure intracranial hemorrhage nor the 90-day mRS was associated with thrombus length or density. Conclusions: We have not found any significant associations between either thrombus length or density and likelihood of recanalization, time to achieve recanalization, intraprocedural complications, postprocedural hemorrhage or functional outcome at 90 days. These results do not support a predictive value for thrombus quantification in the evaluation of AIS.